The Neural Correlate Difference Between Positive and Negative Awe - Fang Guan; Sasa Zhao; Shaona Chen; Shi Lu; Jun Chen; Yanhui Xiang (Frontiers in Human Neuroscience, 2019)
Awe is an emotional response to perceptually vast stimuli that transcend current frames of reference. Narrative and experimental work has characterized two distinct variants of awe: positive and negative; however, little is known about the structural neural basis associated with the differences of these two variants of awe. In this study, we investigated the structural neural basis of positive and negative awe underlying individual differences among 62 young healthy adults. Specifically, we assessed the association between regional gray matter volume (rGMV) and the two different variants of awe using the voxel-based morphometry (VBM). A partial correlation analysis was conducted to examine the relationship between rGMV and behavioral positive and negative awe, while controlling for sex, age and total GMV. VBM indicated that positive awe was positively correlated with GMV in the precuneus, and negatively correlated with GMV in the left fusiform and the right calcarine. Negative awe was negatively correlated with GMV in the left and right insula, and the left superior temporal gyrus. These results provide a neural explanation for the differences of these two variants of awe.